STAKEHOLDER ANALYSIS OF SCHOOL HEALTH PROGRAM AT ELEMENTARY SCHOOLS IN NORTH JAKARTA, A CASE STUDY - Xarisa Azalia; Regina Satya Wiraharja; Hadiyanto (Fakultas Kedokteran Universitas Sriwijaya, 2024)
The School Health Unit (UKS) program has been implemented since 1984. Although this program has been done yearly, the children's health status has not been optimized yet. Studies have been done to evaluate this program, however very limited studies have been done to explore the stakeholders of the program, their roles, and their conflicts, especially at the school level. This study aimed to stakeholder analysis of school health programs at school level. This was a qualitative case study of 4 elementary schools in North Jakarta. Data collection was carried out by means of in-depth interviews. Stakeholder analysis was performed by using steps which consist of identifying stakeholders, identifying interests, analyzing the influence of identified stakeholders and identifying risks, and anticipating risk management. Stakeholder mapping is done using the Grid mapping model. This study shows that in private primary schools, the most influential actors were foundations, namely as “context setters”. In public elementary schools, UKS teachers were the “subjects” and the education authorities were the powerful party in the development of infrastructure. This study also found that there was a conflict between the interests and influence of the main stakeholders, namely foundations and Education Authorities. Foundations and Education Authorities were not directly involved in implementing UKS in schools. This research concludes that the actors have not been maximal in carrying out their roles in the UKS policy at elementary schools in North Jakarta. Cooperation between actors needs to be improved.